10.61533 ANALISIS PRINSIP AKUNTABILITAS, TRANSPARANSI, DAN EFEKTIVITAS DALAM PENGELOLAAN KEUANGAN SEKOLAH DASAR SWASTA SANTA THERESIA I PANGKALPINANG - Angel, Brenda; Novika; Tri Setyo Mulyani, Hendarti (STIE IBEK Pangkalpinang, 2024)
This research is an analysis of the principles of accountability, transparency and effectiveness of school financial management at the Santa Theresia I Pangkalpinang Private Elementary School. This research aims to evaluate the application of the principles of accountability, transparency and effectiveness of school financial management at Santa Theresia I Pangkalpinang Private Elementary School. The method that researchers use is a qualitative descriptive analysis method where data collection uses observation, interview and documentation techniques. In this research, the author interviewed several sources including: School Principal, School Treasurer, and Chair of the School Committee. The research results show that Santa Theresia I Pangkalpinang Private Elementary School has demonstrated a commitment to accountability, legal compliance and integrity in its financial management. However, there are still areas that need improvement, such as increasing information transparency, active involvement of school committees, and evaluating the effectiveness of educational programs. Financial documentation is good but access to information is still limited, and supervision of the use of funds is not optimal. For future research, it is recommended to carry out further evaluation of the implementation of the recommendations proposed in this research. Additionally, the research focus could be expanded to explore the impact of improvements in school financial management on student academic achievement and parental satisfaction. Longitudinal studies can also be conducted to see developments and changes in school financial management practices over time.